Recent Synthetic Applications of the Hypervalent Iodine(III) Reagents in Visible-Light-Induced Photoredox Catalysis - Chen, Chaoyue; Wang, Xin; Yang, Tinghai (Frontiers in Chemistry, 2020)
The synergistic combination of visible-light-induced photoredox catalysis with hypervalent iodine(III) reagents (HIRs) represents a particularly important achievement in the field of hypervalent iodine chemistry, and numerous notable organic transformations were achieved in a mild and environmentally benign fashion. This account intends to summarize recent synthetic applications of HIRs in visible-light-induced photoredox catalysis, and they are organized in terms of the photochemical roles of HIRs played in reactions.